Destruction of Mangrove Vegetation by Sphaeroma terebrans along Kerala Coast - V., Santhakumari (Fishery Technology, 2025)
Extent of damage caused by wood boring isopoad crustaceans to mangrove vegetation off Kerala Coast has been evaluated in this study, based on a survey and monthly collections from two localities in Cochin backwater system. Eventhough the incidence of various borer and fouler species was recorded, Sphaeroma terebrans was found to be the chiefdestroyer of the prop roots and stems of the mangroves of Kerala. The major portions of the mangrove trees had their prop roots cut off at approximately the level of mean high water. Those prop roots that remained were perforated and exhibited all stages of destruction accompaniedby secondary decomposition due to the attack of bacteria and fungi. Numerous individuals,bothjuveniles and adults of S. terebrans were found inside the prop roots and stems.